Evaluation basics - McCain, Donald V. (ATD training basics series., 2016)
Your training: Do they love it or live it? How do training professionals show the impact their programs are making? Positive feedback only goes so far in confirming success. And entertainment value, while important, isn't the truest measure of your effectiveness. To find out whether your participants are applying what they've learned on the job, you need a good evaluation strategy--one that connects evaluation to performance, program design, and bottom-line value. Each chapter of Evaluation Basics focuses on a critical aspect of developing and implementing an evaluation plan for a face-to-face or virtual training program. You'll not only learn about the methods and instruments you can use to determine the value of your program, but you'll also get help effectively communicating results. Part of ATD's Training Basics series, the second edition of Evaluation Basics offers practical examples, worksheets, and new case studies to further your understanding.